2014
DOI: 10.1007/s10803-014-2205-8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Children with Autism Spectrum Disorders (ASDs): A Case–Control Study

Abstract: Children with autism spectrum disorder (ASD) have problems of food selectivity, implying risks of nutritional deficiencies. The aim was to compare intakes of macro and micronutrients and body mass index in ASD and typically developing (TD) children. In a case-control study, 3-day food diaries and anthropometric measurements were completed for ASD (n = 40) and TD (n = 113) children (aged 6-10 years) living in the same area. Body mass indices were below the 5th percentile in 20 % of ASD versus 8.85% of TD childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 48 publications
5
48
1
4
Order By: Relevance
“…Fifteen studies were published between 2010 and 2016 9,2437 . Four studies were case-control 24,27,31,33 and eleven studies were cross-section 9,25,26,28–30,32,3437 . The studies encompassed a total of 49,937,078 participants and 1,045,538 individuals with ASD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies were published between 2010 and 2016 9,2437 . Four studies were case-control 24,27,31,33 and eleven studies were cross-section 9,25,26,28–30,32,3437 . The studies encompassed a total of 49,937,078 participants and 1,045,538 individuals with ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were carried out in the United States 2427,29,30,3437 , two in Brazil 9,31 , one in Turkey 32 , one in Spain 33 , and one in China 28 . The sample sizes ranged from 40 33 to 986,352 30 individuals with ASD and from 19 9 to 48,598,466 30 controls. Additionally, the mean ages of the samples ranged from 2 years old 25,27,34 to 29.4 ± 12.1 years old 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the behavioral rigidity displayed by these individuals can lead to unhealthy eating habits. There are reports of food selectivity presented by these individuals, like consume of a limited range of food items, resistance to try different foods and behavioral problems at mealtime (5). Thus, impaired nutritional status is not unusual in patients with ASD (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…When the normal, overweight and obese categories were considered, the range for potential risk of excess consumption was between 50 to 75% in both studies. A recent study reported intake levels of cholesterol in children with ASD (6-9 years, n=40) that were slightly higher than Spanish recommendations [65]. Children and adolescents with high cholesterol levels are more likely to have high levels as adults when compared to the rest of the population and elevated blood levels are associated with CVD [66,67].…”
Section: Discussionmentioning
confidence: 99%